Endovascular treatment for acute ischaemic stroke due to medium vessel occlusion: data from ANGEL-ACT registry. Issue 1 (1st September 2022) - Sun, Dapeng, Raynald; Huo, Xiaochuan; Jia, Baixue; Tong, Xu; Wang, Anxin; Ma, Gaoting; Ma, Ning; Gao, Feng; Mo, Dapeng; Miao, Zhongrong
Abstract : Objectives: To investigate the safety and efficacy of endovascular treatment (EVT) for acute medium vessel occlusion (MeVO) in the anterior circulation and to explore the independent predictors of the 90-day good outcome for such patients. Methods: Data from ANGEL-ACT Registry were analysed in our study. The outcomes, such as the modified Rankin Scale (mRS) at 90 days, successful recanalisation rate and symptomatic intracranial haemorrhage (SICH) rate, were compared between MeVO and acute large vessel occlusions (LVO). Then, the independent predictors of the good outcome at 90 days in MeVO patients were determined by the logistic regression analyses. Results: We included 1032 subjects in the analysis, of which, 147 were MeVO and 885 were LVO. mRS at 90 days distribution (3 (0–4) vs 3 (0–5), common odds ratio (OR) =1.00, 95% confidence interval (CI) 0.73 to 1.38, p=0.994), SICH rate (4.8% vs 8.9%; OR=0.59, 95% CI 0.26 to 1.34, p=0.205) and successful recanalisation rate (89.8% vs 89.7%; OR=1.00 95% CI 0.51 to 1.93, p=0.992) were similar between the MeVO and LVO groups after adjusting for the confounders. We identified that baseline neutrophil-to-lymphocyte ratio ≤4.1 (OR=2.13, 95% CI 1.14 to 3.99, p=0.019), baseline National Institutes of Health Stroke Scale ≤14 (OR=1.96, 95% CI 1.02 to 3.80, p=0.045) and mechanical thrombectomy passes ≤1 (OR=2.16, 95% CI 1.14 to 4.11, p=0.021) were independent predictors of the 90-day good outcome in MeVO patients undergoing EVT. Conclusions: Patients with MeVO achieved similar 90-day mRS, SICH rate and successful recanalisation rate after EVT compared with patients with LVO. Several independent predictors of 90-day good outcome in MeVO patients undergoing EVT were determined, which should be highly considered in MeVO stroke management.